Failure of reversion of neuromuscular block with sugammadex in patient with myasthenia gravis: case report and brief review of literature - Hermann dos Santos Fernandes; Jorge Luiz Saraiva Ximenes; Daniel Ibanhes Nunes; Hazem Adel Ashmawi; Joaquim Edson Vieira (BMC Anesthesiology, 2019)
Abstract Background Myasthenia gravis (MG) is a challenge for anesthesia management. This report shows that the use of rocuronium-sugammadex is not free from flaws and highlights the importance of cholinesterase inhibitors management and neuromuscular block monitoring in the perioperative period of myasthenic patients. Case presentation Myasthenic female patient submitted to general balanced anesthesia using 25 mg of rocuronium. Under train-of-four (TOF) monitoring, repeated doses of sugammadex was used in a total of 800 mg without recovery of neuromuscular blockade, but TOF ratio (TOFR) was stabilized at 60%. Neostigmine administration led to the improvement of TOFR. Conclusions Although the use of rocuronium-sugammadex seems safe, we should consider their unpredictability in myasthenic patients. This report supports the monitoring of neuromuscular blockade as mandatory in every patient, especially the myasthenic ones.